Nghiên cứu tổng hợp các flavone mới trên cơ sở 2,4-dihydroxyacetophenone - Anh, Nguyễn Lê; Vũ, Trần Khắc (Vietnam Journal of Chemistry, 2014)
A series of new flavone derivatives (4a-g) was synthesized based on 2,4-dihydroxyacetophenone through a three-step procedure. Firstly, the reaction of 2,4-dihydroxyacetophenone (1) with propargyl bromide in acetone under reflux condition for 72 hours using K2CO3 as a catalyst gave the intermediate 2 in 75 % yield. Next, the Claisen Schmidt condensation reaction of 2 with different aldehydes in methanol in the presence of NaOH as a catalyst at room temperature obtained new chalcones 3a-g in 68-82 % yields. Finally, these chalcones were oxidatively cyclized in DMSO in the presence of I2 to furnish new flavones 4a-g in 45-59 % yields. The structure of synthesized compounds was elucidated using IR, NMR. Keywords: Claisen Schmidt, chalcone, 2,4-dihydroxyacetophenone, flavone, propargyl bromide.